Kinetics and Dynamics of Intravenous Anesthetics - Woerlee, Gerald M. (Developments in Critical Care Medicine and Anesthesiolgy,, 1992)
Many drugs used in current anesthetic practice are administered intravenously. An appreciation of their kinetics and dynamics is of great assistance in determining the most appropriate drug to use, and optimal dosage regimens for any given patient. This book is specially oriented to the requirements of anesthesiologists. It will enable the student of those subjects to gain enough knowledge to make these subjects usable in daily anesthetic practice. As such it is intermediate in difficulty between mathematically oriented texts, and those which only offer a very qualitative understanding of these subjects. Practical applications and examples of the uses to which kinetic and dynamic principles can be put in daily practice are emphasized and illustrated. Basic principles and techniques with which the reader can perform kinetic and dynamic calculations are explained simply and demonstrated in detail using examples derived from clinical practice. Two appendices provide kinetic and dynamic data on the most commonly used anesthetic drugs. The last chapters use the principles discussed in the first chapters to show how variations of normal physiology and disease affect drug kinetics and dynamics. This is especially valuable to the clinician as it enables clinically useful, albeit qualitative, predictions to be made of the direction of any change of kinetic and dynamic parameters of drugs due to these factors.